2013
DOI: 10.1002/humu.22382
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SLC26A9 in Patients with CF-Like Lung Disease

Abstract: Diffuse bronchiectasis is a common problem in respiratory clinics. We hypothesized that mutations in the solute carrier 26A9 (SLC26A9) gene, encoding for a chloride (Cl(-)) transporter mainly expressed in lungs, may lead to defects in mucociliary clearance. We describe two missense variants in the SLC26A9 gene in heterozygote patients presenting with diffuse idiopathic bronchiectasis : p.Arg575Trp, identified in a patient also heterozygote for p.Phe508del in the CFTR gene; and p.Val486Ile. Expression of both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
(82 reference statements)
1
26
0
Order By: Relevance
“…Furthermore, a functional single nucleotide polymorphism (rs2282430) in the 39 untranslated region of SLC26A9 that reduced protein expression by creating a binding site for a microRNA (has-miRNA-632) was shown to be associated with asthma in children, and SLC26A9 variants were recently detected in patients with non-CF bronchiectasis [113]. These results suggest SLC26A9 as a modifier and novel therapeutic target in CF and potentially other mucostatic airway diseases, including severe asthma and COPD.…”
Section: Slc26a9-mediated CLmentioning
confidence: 85%
“…Furthermore, a functional single nucleotide polymorphism (rs2282430) in the 39 untranslated region of SLC26A9 that reduced protein expression by creating a binding site for a microRNA (has-miRNA-632) was shown to be associated with asthma in children, and SLC26A9 variants were recently detected in patients with non-CF bronchiectasis [113]. These results suggest SLC26A9 as a modifier and novel therapeutic target in CF and potentially other mucostatic airway diseases, including severe asthma and COPD.…”
Section: Slc26a9-mediated CLmentioning
confidence: 85%
“…CFTR protein function defects are probably a key factor in airway respiratory diseases; but CFTR gene alterations are probably not the main etiology. For instance, mutations in the SLC26A9 gene may prevent the SLC26A9-CFTR interaction and thus CFTR functional activation in CF-like lung disease [30]. Although the role of CFTR in lung diseases, other than CF, is conflicting, genome-wide association studies of COPD [31] and asthma [32] have not identified the CFTR gene as a susceptibility gene.…”
Section: Discussionmentioning
confidence: 98%
“…These results support a role of SLC26A9 as an alternative chloride channel that may contribute to the regulation of airway surface liquid (ASL) essential for mucus clearance under pathophysiological conditions. Third, data emerging from genetic studies in humans provide independent evidence supporting the role of SLC26A9 as a disease modifier in CF and potentially other chronic obstructive lung diseases [83][84][85][86][87]. Specifically, consistent with a protective function of SLC26A9 in Th2-mediated airway inflammation, it was shown that a functional SNP (rs2282430) is associated with asthma in children [83].…”
Section: Slc26a9mentioning
confidence: 91%
“…In the meantime, several additional polymorphisms were identified that alter SLC26A9 function by a variety of molecular mechanisms ranging from altered protein expression to decreased or increased chloride channel activity in vitro [84]. Interestingly, some of these variants were recently detected in patients with CF-like lung disease [85]. Further, SLC26A9 polymorphisms were also found to be associated with the risk to develop meconium ileus and early exocrine pancreatic disease in patients with CF [86,87].…”
Section: Slc26a9mentioning
confidence: 96%